Origanum vulgare ssp. vulgare: Chemical Composition and Biological Studies - Oniga, Ilioara (Molecules, 2018)
The biological properties and main phenolic compounds of the O. vulgare L. ssp. vulgare extract are described in the present paper. The polyphenolic compounds were analyzed by chromatographic and spectrophotometric techniques. The antioxidant potential was evaluated using several methods: CUPRAC (cupric ion reducing antioxidant capacity), FRAP (ferric reducing ability of plasma), inhibition of lipid peroxidation catalyzed by cytochrome c, and superoxide (SO) scavenging assays. The antimicrobial activity of the oregano extract was evaluated by means of agar-well diffusion assay. The hepatoprotective effect of the O. vulgare extract on CCl(4)-induced hepatotoxicity was evaluated in rats. Liver injury was estimated by determination of alanine aminotransaminase (ALT), aspartate aminotransaminase (AST), gamma-glutamyl transferase GGT, total protein and albumin concentrations, glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD) and malondialdehyde (MDA). These values were improved by the administration of oregano extract. A specific phenolic profile was evidenced by these data, with large amounts of rosmarinic and chlorogenic acids. The oregano extract showed very strong antioxidant activity in good agreement with the phenolic content. Antimicrobial activity was good, especially against Salmonella enteritidis and Aspergillus niger strains. The high hepatoprotective, antioxidant and antimicrobial activity, along with polyphenol-rich content, can support the use of O. vulgare in therapy. We also expect our results to open new research directions for designing important new drug products, using indigenous plant material.